Niemonotoniczna logika niefregowska - Wójtowicz, Anna (Filozofia Nauki, 2011)
NonFregean logic is the classical logic enriched by identity connective. In one of possible interpretations of this calculus, the identity connective joins two sentences into a true sentence when these sentences have the same meaning. But when (if any) do simple sentences (i.e. sentences not containing logical constants) have the same meaning? In the paper the non-monotonic version of nonFregean logic is presented. The starting point of every reasoning in this logic is that all simple sentences have the same meaning. This assumption may be retracted in order to maintain consistency with a new piece of information.